1997
DOI: 10.1063/1.474753
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of the structural and electronic properties of ethylene adsorption on Si(100)-(2×1) surface

Abstract: Diels-Alder reactions of butadienes with the Si(100)-2×1 surface as a dienophile: Vibrational spectroscopy, thermal desorption and near edge x-ray absorption fine structure studiesWe present a first-principles density-functional study for ethylene adsorption on the Si͑100͒-͑2ϫ1͒ surface. Ethylene is di-bonded to the surface Si dimers with the adsorption energy of 1.81 eV. The dimer-maintained adsorption structure is found to be more stable than the dimer-cleaved one by 0.91 eV. Our calculations on the post-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 26 publications
6
30
0
Order By: Relevance
“…3͑a͔͒ is found to be more stable than the dimer-cleaved model by ⌬E ads ϭ1.14 eV. This is comparable to the LDA result (⌬E ads ϭ1.11 eV͒ obtained by Pan et al 10 Their LDA values for the adsorption energy are larger than our GGA ones, while the LDA calculations carried out by Fisher et al 11 gave too small an adsorption energy, as mentioned above in adsorbed C 2 H 2 ͑see Table III͒. It is interesting to note that in adsorbed C 2 H 4 the tetra-model is unstable compared to the gas phase.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…3͑a͔͒ is found to be more stable than the dimer-cleaved model by ⌬E ads ϭ1.14 eV. This is comparable to the LDA result (⌬E ads ϭ1.11 eV͒ obtained by Pan et al 10 Their LDA values for the adsorption energy are larger than our GGA ones, while the LDA calculations carried out by Fisher et al 11 gave too small an adsorption energy, as mentioned above in adsorbed C 2 H 2 ͑see Table III͒. It is interesting to note that in adsorbed C 2 H 4 the tetra-model is unstable compared to the gas phase.…”
supporting
confidence: 80%
“…Similarly, we performed the geometry optimization for adsorbed C 2 H 4 on Si͑100͒ within the dimerized, dimercleaved, and tetra-models. The calculated adsorption energies and bond lengths are compared with those of previous calculations [9][10][11] in Table III, together with the experimental data. 5,6 For ϭ1 ML, the dimerized model ͓Fig.…”
mentioning
confidence: 99%
“…For the most strongly bound configuration (a), binding energies of 1.89 and 2.00 eV are reported for ethylene and maleic anhydride, respectively. This value for ethylene is very close to a previously computed value of 1.81 eV [13], obtained also using the PW91 functional, however, for the full monolayer coverage. Both of these values are in reasonable agreement with a value of 1.67 eV for the barrier to thermal desorption of ethylene [14,15], derived from the fully covered Si(1 0 0) surface.…”
Section: Resultssupporting
confidence: 86%
“…Table 1 also shows, most significantly, that the binding of (c) has increased from 0.29 to 1.79 eV as a result of rearrangements of the unreacted silicon atoms in the partially reacted silicon dimers. Similar stabilization has also been found for above-trough binding of norbornadiene [11] (compare, for e.g., the bindings reported for structures 3, 5 and 7 therein) and this effect has also been observed for ethylene chemisorption [13]. Originally [5], it was reasoned that structural rearrangements stabilized above-trough adsorbates and that this effect was significantly coverage dependent.…”
Section: Resultsmentioning
confidence: 55%
“…4 Among the alkenes ethylene was the first molecule for which the adsorption structure on the Si(100)-(2ϫ1) surface was well established by experimental methods such as scanning tunneling microscope ͑STM͒ 5,6 and traditional surface science techniques [7][8][9][10] as well as by theoretical simulations. 11,12 It has been demonstrated that ethylene reacts with the silicon surface via the interaction between the C-C double bond and silicon dimers, producing two Si-C bonds ͑the so-called di-bonding͒. Other alkenes are found to react in a similar fashion with the Si͑100͒ surface, [13][14][15][16][17] i.e., they bind to the surface also via the di-bonding configuration.…”
Section: Introductionmentioning
confidence: 99%